Symbiodiniaceae and Bacterial Microbiome Dynamics Differentially Impact the Survival of Dominant Reef‐Flat Porites Corals - Colin Lock; Therese C. Miller; Colin J. Anthony; Héloïse Rouzé; James Fifer; Grace McDermott; Carlos A. Tramonte; Loreto Paulino; Sarah W. Davies; Laurie Raymundo; Bastian Bentlage (Environmental Microbiology, 2025)
Coral reefs face significant threats across the globe, prompting a surge in restoration efforts aimed at mitigating their global decline. The health, resilience, and adaptability of corals are greatly influenced by their microbial communities, and while the response of coral microbiomes to many environmental stressors has been extensively studied, less is known about their natural dynamics following transplantation, which is an essential process for restoring degraded reef habitats. In this study, we integrated DNA metabarcoding (16S & ITS2) with ecological monitoring to investigate the dynamics of Symbiodiniaceae and bacterial communities in two dominant coral spp., Porites lobata and Porites cylindrica , and their different colour morphs, as they underwent transplantation and an 18‐week acclimatisation period. We saw significant differences in microbial communities between the two Porites spp., outplanting sites, and individual coral colonies, as well as a colour morph‐related difference in P. lobata bacterial communities. We saw reduced relative abundances of Endozoicomonadaceae, specifically from the genus Parendozoicomonas, following transplantation. P. lobata colonies with later Symbiodiniaceae shifts (18 weeks) had lower long‐term survival. Changes in Symbiodiniaceae and bacterial communities have implications for holobiont function and colony survival, which should be considered when designing and implementing coral reef rehabilitation projects.

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Representation of Boundary-Layer Processes in Numerical Weather Prediction and Climate Models - John M. Edwards; Anton C. M. Beljaars; Albert A. M. Holtslag; Adrian P. Lock (Boundary-Layer Meteorology, 2020)

Correction to: Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin‑Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin-Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

Maladaptation and phenotypic mismatch in hatchery‐reared Atlantic salmon Salmo salar released in the wild - R. Stringwell; A. Lock; C. J. Stutchbury; E. Baggett; J. Taylor; P. J. Gough; C. Garcia de Leaniz (Journal of Fish Biology, 2014)
Changes in body shape, fluctuating asymmetry ( FA ) and crypsis were compared among Atlantic salmon Salmo salar fry kept as controls in captivity and those released and subsequently recaptured in the wild according to a before‐after‐control‐impact ( BACI ) design. Hatchery fish that survived in the wild became more cryptic and displayed a much lower incidence of fin erosion and of asymmetric individuals than control fish kept in captivity. Significant differences in body shape were also apparent, and survivors had longer heads, thicker caudal peduncles and a more streamlined body shape than hatchery controls as early as 20 days following stocking, most likely as a result of phenotypic plasticity and non‐random, selective mortality of maladapted phenotypes. Hatchery‐reared fish typically perform poorly in the wild and the results of this study indicate that this may be due to phenotypic mismatch, i.e. because hatcheries generate fish that are phenotypically mismatched to the natural environment.

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Effects of Mining Activities on Heavy Metal Concentrations in Water, Sediment, and Macroinvertebrates in Different Reaches of the Pilcomayo River, South America - A. J. P. Smolders; R. A. C. Lock; G. Van der Velde; R. I. Medina Hoyos; J. G. M. Roelofs (Archives of Environmental Contamination and Toxicology, 2003)

Water resources management in the Aral Basin: a river basin management model for the Syr Darya - S. Heaven; G. B. Koloskov; A. C. Lock; T. W. Tanton (Irrigation and Drainage, 2002)
The Aral Sea environmental crisis has been created by poor water management in the river basins of the Amu Darya and Syr Darya. Nearly all the flow is abstracted for ailing irrigation schemes in the upper and middle basins, for massive river basin transfer schemes, or is lost to evaporation and seepage from reservoirs and canals. The only solution to the crisis in the lower deltas is to allow more water to flow to them. The paper argues that the only practical approach for achieving this in the short to medium term is better water management in the upper and middle river basins, and that a more rational basis for allocating water to meet the needs of all users is urgently required. The paper describes a real‐time water resources management model for the Syr Darya river that has been designed for sustainable planning and management of the water resources to meet the needs of all riparian users. The power and limitations of such models in relation to effective management of the water resources of the Aral Basin are discussed. Copyright © 2002 John Wiley & Sons, Ltd.

The Effect of Lindane on Terrestrial Invertebrates - K. Lock, K. A. C. De Schamphelaere, C. (Archives of Environmental Contamination and Toxicology, 2002)

Neurotoxic effect of L-2-chloropropionic acid on primary cultures of rat cerebellar granule cells - Nicholas C. Sturgess; Anne Rustad; Frode Fonnum; Edward A. Lock (Archives of Toxicology, 2000)

The role of glutathione S-transferase- and cytochrome P450-dependent metabolism in the olfactory toxicity of methyl iodide in the rat - M. P. Chamberlain; E. A. Lock; B. A. Gaskell; C. J. Reed (Archives of Toxicology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Olfactory toxicity of methyl iodide in the rat - C. J. Reed; B. A. Gaskell; K. K. Banger; E. A. Lock (Archives of Toxicology, 1995)

Effects of water-borne cadmium on the skin of the common carp (Cyprinus carpio) - Y. Iger; R. A. C. Lock; J. C. A. van der Meij; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1994)

Effect of waterborne and dietary cadmium on plasma ions of the teleostOreochromis mossambicus in relation to water calcium levels - H. B. Pratap; H. Fu; R. A. C. Lock; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1989)

Calmodulin-mediated cadmium inhibition of phosphodiesterase activity, in vitro - Gert Flik; Jan G. J. van de Winkel; Peter Pärt; Sjoerd E. Wendelaar Bonga; Robert A. C. Lock (Archives of Toxicology, 1987)